Electronic and fluorescent studies on the interaction of DNA and BSA with a new ternary praseodymium complex containing 2, 9-dimethyl 1, 10-phenanthroline and antibacterial activities testing. Issue 9 (13th June 2019) - Moradi, Zohreh; Khorasani-Motlagh, Mozhgan; Rezvani, Ali Reza; Noroozifar, Meissam
Abstract: In this study, fluorescence emission spectra, UV–vis absorption spectra, ethidium bromide (EB)-competition experiment, and iodide quenching experiment were used for the interaction study of the Fish salmon DNA (FS-DNA) with [Pr(dmp)2Cl3(OH2)] where dmp is 2, 9-dimethyl 1, 10-phenanthroline. The binding constant and the number of binding sites of the complex with FS-DNA were 6.09 ± 0.04 M −1 and 1.18, respectively. The free energy, enthalpy, and entropy changes (Δ G °, Δ H °, and Δ S °) in the binding process of the Pr(III) complex with FS-DNA were –8.02 kcal mol −1, +39.44 kcal mol − 1, and +159.56 cal mol −1 K −1, respectively. Based on these results, the interaction process between FS-DNA with [Pr(dmp)2Cl3(OH2)] was spontaneous and the main binding interaction force was groove binding mode. Also, Fluorescence and electronic absorption spectroscopy were used in order to evaluate the binding characteristics, stoichiometry, and interaction mode of praseodymium(III) (Pr(III)) complex with bovine serum albumin (BSA). Title complex showed good binding propensity to BSA presenting moderately high Kb values. The fluorescence quenching of BSA by Pr(III) complex has been observed to be the static process. The positive Δ H ° and Δ S ° values showed that the hydrophobic interaction is the main force in the binding of Pr(III) complex and BSA. Eventually, the average aggregation number, < J >, of BSA potentially induced by title complex confirmed the 1:1 stoichiometry for title complex-BSA adducts. In vitro, antimicrobial activity of title complex was indicated that the complex is more active against both Escherichia coli and Enterococcus faecalis bacterial strains than Staphylococcus aureus, and Pseudomonas aeruginosa. Communicated by Ramaswamy H. Sarma